Liquidity constraints and collateral crises - Rodrigues, Diego de Sousa (2018)
Asset-backed securities were widely traded. Arguably, this happened because they were complicated claims, in the sense that it was very costly to assess their fundamental value. Here, we show that if this is the case, then the emergence of alternative ways to address liquidity needs, by undermining the liquidity role of these assets and reinforcing the relevance of their fundamental value, may increase the incentives to acquire information about them, and negatively impact the credit market. Hence, our results suggest that it is easier for these assets to accomplish the role of private money when there are fewer alternative ways to address liquidity needs.